Novel markers in the diagnostics of endometriomas: Urocortin, ghrelin, and leptin or leukocytes, fibrinogen, and CA-125? - Karolina Chmaj-Wierzchowska; Małgorzata Kampioni; Maciej Wilczak; Stefan Sajdak; Tomasz Opala (Elsevier, 2015)
Objective: CA-125 protein is used as a marker in clinical practice for the diagnosis of endometriomas. The aim of this study was to determine whether endometriomas are accompanied by an increased level of urocortin, ghrelin, and leptin, as well as the increased parameters of blood cell count, fibrinogen, and CA-125. Materials and methods: The study included 86 women aged 18-38 years who had been treated laparoscopically for lesions in the adnexa with the characteristics of endometriomas and mature teratoma, during the period September 2009 to November 2012. The statistical analysis was performed using the nonparametric Mann-Whitney U test and the Spearman rank correlation coefficients (p ≤ 0.05). Results: The medians were 105.31 pg/mL versus 120.84 pg/mL for urocortin, 7.16 pg/mL versus 9.13 pg/mL for leptin and 584.33 pg/mL versus 657.82 pg/mL for ghrelin (p > 0.05), respectively. Analyzing the parameters of blood cell count, statistically significant differences were shown in the respective groups for leucocyte level (5.35 × 109/L vs. 6.7 × 109/L; p = 0.029), fibrinogen level (3.12 mg% vs. 2.57 mg%; p = 0.001), and CA-125 (36.50 U/mL vs. 15.08 U/mL; p = 0.001). Conclusion: In conclusion, the prognostic values for CA-125, leukocytes, and fibrinogen may prove a very useful tool for the diagnosis of lesions in the adnexa of the type endometriomas.